SIGNIFICANCE OF CHEST PAIN WITHOUT ST CHANGES DURING EXERCISE TREADMILL TESTING - Akbar, Ahmad Masood; Hameed, Shahid; Azhar, Muhammad; Sheikh, Saqib Shafi; Sattar, Abdul; Naveed, Tahir (Journal of Ayub Medical College Abbottabad, 2010)
Background: Exercise treadmill test is interpreted as positive or negative for ischemia in the presence or absence of ST depression respectively. This study was conducted to evaluate the diagnostic value of chest pain without ST depression during exercise treadmill test. Methods: A total of 180 patients who had abnormal exercise treadmill test result and subsequently underwent coronary angiography were studied. Patients were categorised as having ST depression and angina (group A), only ST depression (group B) and only angina (group C). Coronary angiograms of all patients were assessed and compared. Results: Out of 180 patients [159 (88.3%) men and 21 (11.7%) women], 84 patients were in Group A, 64 in Group B and 32 in Group C. Characteristics like age, sex distribution and risk factors were similar in three groups. Significant coronary artery disease was seen in 77 (91.7%), 40 (62.5%) and in 25 (78.1%) patients in groups A, B and C respectively (p=0.02). Triple vessel disease was seen in 21 (25%), 11 (17.2%) and 5 (15.6%) patients in groups A, B and C respectively. Significant disease of left anterior descending artery was seen in 61 (72.6%), 26 (40.6%) and 23 (71.9%) in groups A, B and C respectively (p=0.001). Conclusion: Occurrence of both ST depression and angina during exercise treadmill test has strong association with angiographic coronary artery disease whereas occurrence of either of the two has similar association with angiographic coronary artery disease with a trend towards more disease in the latter. Keywords: Exercise treadmill test, Angina, Coronary angiography, Coronary artery disease